Changes in the Success and Characteristics of Tobacco Dependence Treatment before and during the COVID-19 Pandemic: Clinical Sample Comparisons - Stepankova, Lenka; Zvolska, Kamila; Pankova, Alexandra; Rafl, Jakub; Donin, Gleb; Tichopad, Ales; Kralikova, Eva (Medicina (Kaunas, Lithuania), 2024)
Background and Objectives: There is little information on changes in the process and outcomes of intensive tobacco dependence treatment during the COVID-19 pandemic. The following characteristics were evaluated: interest in treatment, the number of face-to-face or telephone follow-ups, the duration of pharmacotherapy use, and the success rate. The aim of our study was to compare the number of patients who entered tobacco dependence treatment programmes and evaluate the one-year success rate in patients three years before and three years after the COVID-19 pandemic. Materials and Methods: A single-site retrospective cohort study using data from patients treated at the Centre for Tobacco Dependence in Prague, Czech Republic, between 2017 and 2022 (n = 2039) was performed. The one-year abstinence rate was validated by measuring carbon monoxide in exhaled air (6 ppm cut-off). Patients were divided into two groups: the group for which treatment was initiated in 2017-2019 (i.e., before the COVID-19 pandemic, BC; n= 1221) and the group for which treatment was initiated in 2020-2022 (i.e., during the COVID-19 pandemic, DC; n = 818). Results: No significant differences in the success rate of tobacco dependence treatment were found between the two groups (BC group, 40.5% (494/1221) vs. DC group, 42.2% (345/818)) (χ2 (1, N = 2.039) = 0.6, p = 0.440). Furthermore, differences were not found in sex, education level, age at first cigarette, the duration of pharmacotherapy use, or the number of in-person visits. In contrast, there was an increase in the number of telephone contacts between the groups (18.7% (SD = 17.5%) vs. 32.9% (SD = 18.2%), p < 0.001). Conclusions: The number of patients who started treatment during the COVID-19 pandemic decreased by one-third compared to that during the 3-year period before the pandemic. The overall treatment success rate did not change significantly even with the increase in the number of telephone visits with the therapist.
Keywords: dospělí; Female; SARS-CoV-2; Tobacco Use Disorder; Adult; výsledek terapie; ženské pohlaví; lidé; odvykání kouření; Treatment Outcome; COVID-19; pandemie; retrospektivní studie; Male; Czech Republic; poruchy vyvolané užíváním tabáku; Česká republika; lidé středního věku; mužské pohlaví; Retrospective Studies; Pandemics; Middle Aged; Smoking Cessation; Humans